GAME EDUKASI PENGENALAN TEKNOLOGI INFORMASI DAN KOMUNIKASI BERBASIS ANDROID - Azwar Azwar; Hamria Hamria; Mohamad Nur Setiawan Kaharu (JURNAL ILMIAH INFORMATIKA, 2020)
The development of technology in this millennial era has a profound effect on the world of information technology. In the field of education the use of information and communication technology can provide solutions and ease in conducting the learning process, and as a tool to master a competency in the form of a computer. This educational game research can be implemented as seen from the results of tests conducted using the user acceptance testing method conducted on 10 students as samples that get an average score of 9 can be concluded that this Educational Information & Communication Technology Game is Interesting, easy to understand, easy to operate , support policies, help / facilitate, this application is good, good documentation, sophisticated application technology, free of errors and needs to be implemented.